Metahuman AI as a New Media in Mass Communication : (Phenomenological Study at Nike Ardilla's Metahuman Concert at Synchronize Fest 2024) - Husnita, Husnita (Universitas 17 Agustus 1945 Surabaya, 2025)
This study examines the use of Metahuman AI technology in music concerts, with a case study of the virtual performance of Nike Ardilla at Synchronize Fest 2024. The main focus is to explore how the presence of metahumans as a new medium influences fan behavior and the dynamics of digital mass communication. This research employs a phenomenological approach (Schutz, 1967) using qualitative methods through in-depth interviews, observations, and social media content analysis of fans. The theoretical framework of this study refers to Digital Mass Communication Theory (McQuail, 2010), which emphasizes interactivity, virtuality, and media convergence; the concept of Mediated Presence (Couldry & Hepp, 2017), which views media as a social environment; and Convergence Culture (Jenkins, 2006), which explains the shifting relationship between media, technology, and audiences. The findings reveal that Metahuman AI serves not only as an entertainment medium but also as a collective identity construction that extends the digital existence of artists. This study shows that digital mass communication has shifted from merely transmitting information to becoming an immersive experiential space, where technology functions as both a cultural and emotional actor. Keywords: Metahuman AI, digital mass communication, phenomenology, fans, popular culture